Practicing English Communication to Promote Batik Enem at SMKN 6 Jember - Pramudita, Rizqi Febrian; Kamal , Mushthofa; Taufan , Gullit Tornado; Suharsono , Degita Danur; Wicaksono , Julien Arief (Journal Of Humanities Community Empowerment, 2025)
Batik activities at SMKN 6 Jember have been running since the 2021/2022 academic year, hosted at the Batik and Textile Creative Crafts (KKBT) major. Their signature product, “Batik Enem”, is quite well-known in Jember regency and has also contributed to the talent of a big annual event, Jember Fashion Carnival (JFC). However, a passion exists to market this product to a higher level and be widely known. The expected step is that the role of students who are involved in Batik Enem can communicate using English to promote this product to the general public, even abroad. Therefore, this program was created to provide English communication training to students at SMKN 6 Jember, involving several selected students from the KKBT major. The community service method used project-based learning by having pair work and role-play. The results of this community service activity were that students can communicate using English, especially by describing and carrying out buying and selling practices related to Batik Enem products